Dynamics of workload and burnout among nurses in the intensive care unit during COVID-19 pandemic - Saud Abdullah Aljanfawi (Hail Journal of Health Sciences, 2022)
Introduction: The global shortage and increase in the demand for health-care needs put the nurses under extra pressure in facing the pandemic, especially those who work in critical areas. Thus, the turnover among them increased significantly. Objective: This study aims to determine the factors that influence the workload and burnout among nurses in the intensive care unit (ICU) during the COVID-19 pandemic. Methods: The study was conducted between November and December 2021 using a quantitative-correlational design. The sample was taken randomly with 119 ICU nurses from the government hospitals of the Hail region, Saudi Arabia. One-way ANOVA, t-test, and bivariater were used to analyze the data. Results: The nature of the activity was reported as the highest stressor factor affecting the workload (4.76/5). There was a high degree of occupational exhaustion (OE) (31.13), a moderate degree of depersonalization (10.89), and personal accomplishment (PA) (27.95). Gender and civil status were found to have no significant impact on workload and burnout (P > 0.05). Meanwhile, the years of experience were found to have a significant effect on the workload (component of structure [F = 3.338; P = 0.043]; component of process [F = 2.115; P = 0.020]; and component of activity [F = 3.895; P = 0.026]) but not in burnout (P > 0.05). Further, there was a positive significant relationship between the components of structure and OE (r = 0.257; P = 0.049), PA (r = 0.291; P = 0.025), component of process and OE (r = 0.315; P = 0.015). Conclusion: The type of activity was found to cause high stress for ICU nurses. Moreover, third of the sample reported having a high level of OE. There was a moderate level of depersonalization and PA. Thus, more attention should be given to improve the satisfaction among ICU nurses to decrease the level of burnout.